THE RELATIONSHIP BETWEEN THE ROLE OF FARMER GROUPS AND THE WELFARE OF THEIR MEMBERS IN BANYU ABANG VILLAGE, TELUK BATANG DISTRICT, KAYONG UTARA REGENCY - Wiwik Indrayani; Komariyati Komariyati; Shenny Oktoriana (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
Farmer groups act as learning classes, collaboration platform and production units. Welfare is the goal of farming families, where prosperity is the ability to meet the food and non-food needs of farming households and manage expenses. The aim of this research is to determine the level of the role of farmer groups and the welfare of their members, as well as to analyze the relationship between the role of farmer groups and the welfare of farmer group members in Banyu Abang Village, Teluk Batang District, North Kayong Regency. The population in this study was 360 members, with a sample size of 100 farmers. The data collection techniques used were direct observation and interviews with farmers. The data analysis used was Spearman's Rank Correlation analysis using IBM SPSS Statistics 23 software. The results of the study showed that the majority of farmers spent most of their income on food consumption, which reached 55.3% of total income and more than 70% of farmer family expenses were spent on food consumption, especially rice and daily necessities. Based on the results of the Spearman rank statistical test, Poktan's role as a learning class, collaboration vehicle, and production unit has a positive but weak relationship with the level of welfare of members. The correlation value between learning classes (0.307), collaboration platform (0.292), and production units (0.302) shows that although there is a positive relationship, the relationship to member welfare is not very strong. This means that although farmer groups can have a positive impact, their role has not been strong enough to significantly improve welfare.